Efetividade regulatória para a universalização dos serviços de abastecimento de água e esgotamento sanitário na região metropolitana de Goiânia - Cunha, Danilo Guimarães (2020)
Universalization is the guiding principle of sanitation, and the presence of a regulatory body is a normative imposition. This public service is characterized by the vulnerability of the consumer-user, given the characteristic monopoly of this essential service. The challenge is even greater for expansion in metropolitan regions with neighboring Municipalities. The institutional arrangement of metropolitan regions was brought to state competence without homogeneity at the national level, bringing challenges to inter-federative governance. Although the holder of the local service is the Municipality, the Supreme Federal Court laid the foundations at the regional level, allowing for compulsoriness. In this scenario, we seek to understand whether the regulation has been effective for the universalization of sanitation in the Metropolitan Region of Goiânia. The research had an exploratory character of national and regional legislative production, adding jurisprudence and literature on the subject, using the technique of bibliographic research. In order to carry out the formative evaluation, an empirical research was carried out with data from the National Sanitation Information System. There is a lack of homogeneity in the provision of services in this region, with municipalities showing good rates and other bad rates, and in comparison with the last 10 years of the data available in order to carry out the prospective analysis, we found that the progressive expansion should be enhanced. We seek to point out that the regulatory entity must be unique, because when understanding the normative structure and the competences, it is observed that the non-integration of the system, with a single regulatory entity, would be harmful to the population directly interested. The State and Metropolitan Plans have not yet been formalized, which to some extent undermines regulatory action, which has not yet been defined by the metropolitan entity, although there is a state regulatory agency and a municipal regulatory agency in the capital.